Bridging Eras: integrating ancient remedies with modern biotechnology to combat Non-TB skin infections - Teli, Nisargkumar; Upadhyay, Kinjal (Frontiers in Natural Products, 2025)
The rising global concern of antibiotic resistance has renewed scientific interest in understanding and exploring the traditional remedies as alternative or complementary therapeutics. Ancient medical systems such as Ayurveda have used plant-based systems such as Neem, turmeric for their anti-inflammatory, antimicrobial and/or wound healing actions. Non-tuberculosis mycobacteria (NTM), a diverse group of mycobacterial species excluding Mycobacterium tuberculosis, are increasingly recognised as important causes of chronic skin and soft tissue infections. These infections are specifically challenging as the NTM species often invade deeper layers of the skin, exhibiting high levels of intrinsic antibiotic resistance and are frequently difficult to diagnose in early stages of infections. As a result of this, treatment failures are often, and hence there is a growing interest in sustainable, natural and less toxic treatment options. This leads to the need for scientifically backed ancient knowledge as a potential solution for these kinds of infections. Modern biotechnology could provide innovative ways to enhance the clinical utility of such natural or ancient compounds by addressing the limitations, like poor solubility, low stability and restricted tissue penetration. Modern biotechnology could enhance bioavailability and allow controlled as well as targeted release at infected sites. Therefore, the integration of traditional or ancient plant-derived therapeutics with advanced biotechnology holds a significant promise for developing safer, more effective and sustainable treatment approaches against NTM-related skin infections. The upcoming part hence focuses on bridging ancient remedies with modern biotechnology for their combined potential advantages and some real-life applications with prospects with regard to the management of non-TB mycobacterial skin infections.